Heme Deficiency in Alzheimer's Disease: A Possible Connection to Porphyria. (25th June 2006) - Dwyer, Barney E.; Stone, Meghan L.; Zhu, Xiongwei; Perry, George; Smith, Mark A.
Abstract : Mechanisms that cause Alzheimer's disease (AD), an invariably fatal neurodegenerative disease, are unknown. Important recent data indicate that neuronal heme deficiency may contribute to AD pathogenesis. If true, factors that contribute to the intracellular heme deficiency could potentially alter the course of AD. The porphyrias are metabolic disorders characterized by enzyme deficiencies in the heme biosynthetic pathway. We hypothesize that AD may differ significantly in individuals possessing the genetic trait for an acute hepatic porphyria. We elaborate on this hypothesis and briefly review the characteristics of the acute hepatic porphyrias that may be relevant to AD. We note the proximity of genes encoding enzymes of the heme biosynthesis pathway to genetic loci linked to sporadic, late-onset AD. In addition, we suggest that identification of individuals carrying the genetic trait for acute porphyria may provide a unique resource for investigating AD pathogenesis and inform treatment and management decisions.